2007
DOI: 10.1590/s1415-52732007000400003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores demográficos e comportamentais associados à obesidade abdominal em usuárias de centro de saúde de Belo Horizonte, Minas Gerais, Brasil

Abstract: OBJETIVO: Identificar variáveis sócio-demográficas e comportamentais potencialmente associadas à obesidade abdominal, em mulheres usuárias de unidade básica de saúde. MÉTODOS: Foram investigadas 827 mulheres entre 12 e 65 anos, residentes na região Metropolitana de Belo Horizonte, Minas Gerais, Brasil, utilizando-se desenho transversal. A obesidade abdominal foi definida como valores de circunferência da cintura >88cm. A associação entre obesidade abdominal e as covariáveis foi avaliada por meio da técnica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
2
10
0
10
Order By: Relevance
“…The problem, however, begins early, because more than 30% of the women with less than 30 years of age already had excess weight and/or abdominal obesity, which in the age group between 30-40 years already affected half the women. This association, however, was found in several studies (3,(5)(6)11,(13)(14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 74%
“…The problem, however, begins early, because more than 30% of the women with less than 30 years of age already had excess weight and/or abdominal obesity, which in the age group between 30-40 years already affected half the women. This association, however, was found in several studies (3,(5)(6)11,(13)(14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 74%
“…A paridade tem sido constantemente identificada como fator de risco 3,14,19 , embora não tenha sido identificada associação neste estudo. Por outro lado, fatores obstétricos como a idade de menarca e a idade ao primeiro parto não têm sido consistentemente investigados.…”
Section: Resultsunclassified
“…A associação com a idade prematura ao primeiro parto revelada neste trabalho, poderia ser atribuída à ativação precoce dos hormônios relacionados ao ciclo reprodutivo, propiciando assim um aumento da concentração de gordura corporal 20 . Oliveira et al 19 , ao analisarem os fatores associados à obesidade abdominal em mulheres usuárias de um Centro de Saúde de Belo Horizonte, Minas Gerais, não verificaram associação.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…This result is in contrast with the findings of a study in the city of Florianópolis, SC, Brazil, which found lower prevalence of abdominal obesity according to WHtR among women with higher educational levels 13 . Other studies have also found an increased probability of overweight, obesity 6,22 and abdominal obesity according to WC 28,29 , among women with lower educational levels. As can be seen in the literature, it is generally expected that prevalence rates of excess weight and abdominal obesity will be lower among people with higher levels of education, on the basis that it is assumed that they know more about the importance of healthy habits 30 .…”
mentioning
confidence: 86%